PENGARUH PELATIHAN MENGGUNAKAN MODUL TENTANG KANKER PAYUDARA TERHADAP PENGETAHUAN, MINAT DAN PERILAKU DALAM MELAKUKAN PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA WANITA USIA 20-40 TAHUN DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA (DIY) - Yustiana Olfah (Universitas Muhammadiyah Semarang, 2014)
Background:Breast cancer is a malignant tumor from the breast glands, lymph channels and supporting breast tissue and can cause death in women. Breast cancer is one of the abnormalities in the breast that is often feared. Statistics show that more women worldwide develop breast cancer than any other type of cancer risk factors were related to the incidence of breast cancer and has been widely accepted by the cancer specialist (oncologist) in the world, namely age, unmarried, age of first birth, age of menarche,age of menopause, history of illness, family history, oral contraceptives (Hawari, 2004). Various ways of preventing the risk of breast cancer, by providing training modules along with leaflets about breast cancer and how early detection by breast self-examination.Objective:Knowing the influence of training using the modules on breast cancer knowledge, interests and behavior in performing breast self-examination (BSE) in women aged 20-40 years in DIYMethods:Quasi-experimental research is